Validation of semi-quantitative methods for DAT SPECT: influence of anatomical variability and partial volume effect. (17th July 2015) - Gallego, J; Niñerola-Baizán, A; Cot, A; Aguiar, P; Crespo, C; Falcón, C; Lomeña, F; Sempau, J; Pavía, J; Ros, D
Abstract: The aim of this work was to evaluate the influence of anatomical variability between subjects and of the partial volume effect (PVE) on the standardized Specific Uptake Ratio (SUR) in [ 123 I]FP-bib SPECT studies. To this end, magnetic resonance (MR) images of 23 subjects with differences in the striatal volume of up to 44% were segmented and used to generate a database of 138 Monte Carlo simulated SPECT studies. Data included normal uptakes and pathological cases. Studies were reconstructed by filtered back projection (FBP) and the ordered-subset expectation-maximization algorithm. Quantification was carried out by applying a reference method based on regions of interest (ROIs) derived from the MR images and ROIs derived from the Automated Anatomical Labelling map. Our results showed that, regardless of anatomical variability, the relationship between calculated and true SUR values for caudate and putamen could be described by a multiple linear model which took into account the spill-over phenomenon caused by PVE ( for caudate and ≥0.980 for putamen) and also by a simple linear model ( R 2  ≥ 0.952 for caudate and ≥0.973 for putamen). Calculated values were standardized by inverting both linear systems. Differences between standardized and true values showed that, although the multiple linear model was the best approach in terms of variability (  ≥ 11.79 for caudate and  ≤7.36 for putamen), standardization based on a simple linear model was also suitable (  ≥ 12.44 for caudate and  ≤12.57 for putamen).